(untitled) (E Conference Zone, 2022)
This article provides information on ways of visualizing instructional materials in higher education and using the visual capabilities of modern programming languages in the creation of e-learning manuals. As a modern programming language, the possibilities, advantages and disadvantages of the Java language and the visual environment of Android Studio software are mentioned